A 24-hour ambulatory ecg monitoring in assessment of qt interval duration and dispersion in rowers with physiological myocardial hypertrophy - Lutfullin, I.; Kim, Z.; Bilalova, R.; Tsibulkin, N.; Almetova, R.; Mudarisova, R.; Ahmetov, I. (Biology of Sport, 2013)
Myocardial hypertrophy (MH) due to cardiac pathology is characterized by an increase in QT interval duration and dispersion, while the findings for exercise-induced myocardial hypertrophy are contradictory. The majority of published research findings have not explored this relationship, but there have only been a few conducted studies using 24-hour ECG monitoring. The aim of the study was to determine the QT interval duration and dispersion in short-term and 24-hour ECG in endurance athletes with myocardial hypertrophy and without it. Methods: A total of 26 well-trained rowers underwent a resting 12-lead ECG, 24-hour ECG monitoring and echocardiography. Results: Athletes with MH (n = 7) at rest did not show any increase in QTc interval duration and dispersion, or mean and maximal QTc duration in Holter monitoring compared to athletes without MH (n = 19). Left ventricular mass was not significantly correlated with any QTc characteristics. Furthermore, athletes with MH had significantly longer mean QT (P = 0.01) and maximal QT (P = 0.018) intervals in Holter monitoring and higher 24-hour heart rate variability indexes due to stronger vagal effects. Conclusions: The present study demonstrated that athlete`s heart syndrome with myocardial hypertrophy as a benign phenomenon does not lead to an increase in QT? interval duration, or increases in maximal and mean duration in a 24-hour ECG. An increase in QT interval duration in athletes may have an autonomic nature.